Effect of one step temperature increment from mesophilic to thermophilic anaerobic digestion on the linked pattern between bacterial and methanogenic communities. (November 2019) - Lv, Zuopeng; Wu, Xiayuan; Zhou, Bingqian; Wang, Yan; Sun, Ying; Wang, Yanfang; Chen, Zhongbing; Zhang, Jianfeng
Highlights: δ 13 CH4 reflected the methanogenic pathway changes during temperature increase. The decline link was found in Methanomicrobiaceae and Firmicutes affiliated families. Microbial redundancy was the main reason to ensure the δ 13 CO2 stability. Abstract: Process fluctuation caused by temperature modification of anaerobic digestion is routinely monitored via operational parameters, such as pH and gas production, but these parameters are lagging on microbial community performance. In this study, 13 C isotope fractionation in CH4 and CO2 of biogas together with microbial community dynamics were applied to evaluate process stability in response to temperature increment. Results showed that the weakening correlated links between Firmicutes affiliated families and Methanomicrobiaceae were found regarding temperature increase. In contrast, Methanosarcinaceae and Methanobacteriaceae strengthened their links with multiple bacterial groups. This suggests that the 13 C isotope fractionation in CH4 can predict the collapse of certain microbial interconnections and process instability, the new reinforced microbial links directly reflect the microbial community redundancy for maintaining function of syntrophic populations.